Arrival of Young Talent: The Send-Down Movement and Rural Education in China - Chen, Yi; Fan, Ziying; Gu, Xiaomin; Zhou, Li-An (American Economic Review, 2020)
This paper estimates the effects on rural education of the send-down movement during the Cultural Revolution, when about 16 million urban youth were mandated to resettle in the countryside. Using a county-level dataset compiled from local gazetteers and population censuses, we show that greater exposure to the sent-down youths significantly increased rural children’s educational achievement. This positive effect diminished after the urban youth left the countryside in the late 1970s but never disappeared. Rural children who interacted with the sent-down youths were also more likely to pursue more-skilled occupations, marry later, and have smaller families than those who did not. (JEL I21, J13, J24, N35, O15, P36, R23)